2012
DOI: 10.5469/neuroint.2012.7.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient (Same-day care) Neuroangiography and Neurointervention

Abstract: PurposeThere have been few reports regarding same-day discharge following uncomplicated procedures such as cerebral angiography and neurointervention. We present same-day experience with cerebral angiography and neurointervention during the past three years.Materials and MethodsFour hundred and fifty-three patients underwent cerebral angiography or neurointervention at Asan Medical Center between January 2009 and December 2011. Of these patients, 249 (55%) underwent diagnostic catheter cerebral angiography and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
(12 reference statements)
1
11
1
Order By: Relevance
“…The median LOS in our study was 2.52 days, with 26.8% discharged on the day after the procedure (LOS <2 days); this is similar to the findings of other studies 8 17. The mean±SD LOS in our study was 3.99±6.1 days, which is slightly shorter than that reported by Hoh et al in the USA (4.5±7 days) 8.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The median LOS in our study was 2.52 days, with 26.8% discharged on the day after the procedure (LOS <2 days); this is similar to the findings of other studies 8 17. The mean±SD LOS in our study was 3.99±6.1 days, which is slightly shorter than that reported by Hoh et al in the USA (4.5±7 days) 8.…”
Section: Discussionsupporting
confidence: 89%
“…The mean±SD LOS in our study was 3.99±6.1 days, which is slightly shorter than that reported by Hoh et al in the USA (4.5±7 days) 8. The mean LOS after intracranial interventional procedures in a more recent study was shorter (3.1 days) 17. However, that patient population was more heterogeneous and the type of intervention was not clearly defined.…”
Section: Discussioncontrasting
confidence: 75%
“…All UIAs were primarily identified by routine examinations using CTA or MRA. A final diagnosis was established on the basis of digital subtraction angiography (DSA), including 3D rotational angiography [ 7 ]. Five patients exhibited multiple aneurysms, either with two (n = 3), three (n = 1), or four (n = 1) aneurysms.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study showed that same-day care management of outpatients who underwent neuroangiography and neurointervention for various neurovascular diseases provided a shorter admission process and duration on an outpatient basis [ 16 ]. In this report, we present the process, outcome and duration of hospital stay for the management of UIAs via the Neurointervention Clinic over the past four years.…”
mentioning
confidence: 99%